Fabric bending behaviour testing instrument for technical textiles. (June 2016) - Sengupta, Surajit; Debnath, Sanjoy; Sengupta, Anindita
Abstract: Bending is a quiet common phenomenon and affects the performance of textiles. Technical textiles are subjected to different magnitude of bending force depending on applications. Hence, complete bending behaviour study is essential. Hence, an attempt has been made to develop a low cost mechanized and computerised system to study complete behaviour of bending specially for technical textiles. The modified hanging ring loop principle has been adopted to develop this instrument. The developed instrument expresses the bending behaviour in terms of change in bending load/stress/modulus after a certain bending deflection. Various technical textiles like nonwoven, tarpaulin, coated fabrics, canvas, hessian, etc., have been tested with the developed instrument. This instrument can measure dynamic bending behaviour by graphical bending load–deflection, cyclic bending, bending stress relaxation, etc. Statistical analysis like standard deviation and coefficient of variation can be reported. Hence, complete information of bending is available with this instrument. Data and graphs can be stored and printed. It shows reliable results when compared with standard instrument like Shirley Stiffness Tester. The same sample has been tested for 30 times and the deviation between minimum and maximum values was insignificant at 1% level. This instrument is user friendly, low cost and informative for technical textiles. Flexural rigidity and bending modulus can be calculated using standard formula from the available data.